Pelatihan Penyusunan Soal Matematika Berbasis Keterampilan Berpikir Tingkat Tinggi untuk Guru SMA di Kabupaten Magetan - Pradnyo Wijayanti; Ratu Mauladaniyati; Lisnani Lisnani; Heri Purnomo; Sumarni Sumarni; Hilma Alia; Rahma Noviari (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
This Community Service Program aims to improve the competency of high school mathematics teachers in Magetan Regency in developing questions based on Higher Order Thinking Skills (HOTS). The training is designed to provide a deep understanding of HOTS concepts, including cognitive levels C4 (analysis), C5 (evaluation), and C6 (creation), and to equip teachers to design contextual, relevant questions that meet students' needs. With this approach, teachers are expected to produce questions that not only assess students' basic abilities but also foster their critical, creative, and analytical thinking. The training will be conducted through several stages: HOTS concept socialization, a question development workshop, classroom simulations, and post-training mentoring. Teachers will be trained to develop question outlines, select engaging contextual stimuli, and develop HOTS-based questions in accordance with the Merdeka Curriculum and Minimum Competency Assessment (MCA) standards. Additionally, a questionnaire will be used to assess teachers' understanding of the training material. Participants found this activity highly beneficial in improving teacher competency, both in material delivery, question development, and knowledge of the latest curriculum.